STING agonists activate latently infected cells and enhance SIV-specific responses ex vivo in naturally SIV controlled cynomolgus macaques - Yamamoto, Takuya; Kanuma, Tomohiro; Takahama, Shokichi; Okamura, Tomotaka; Moriishi, Eiko; Ishii, Ken J.; Terahara, Kazutaka; Yasutomi, Yasuhiro (Scientific reports, 2019)
To achieve a functional cure for HIV, treatment regimens that eradicate latently HIV-infected cells must be established. For this, many groups have attempted to reactivate latently-infected cells to induce cytopathic effects and/or elicit cytotoxic T lymphocyte (CTL)/NK cell-mediated immune responses to kill these cells. We believe that not only the reactivation of latently-infected cells, but also the induction of strong CTL responses, would be required for this. Here, we used typical immune activators that target pattern recognition receptors (PRRs). For our experimental model, we identified eight SIV-infected cynomolgus monkeys that became natural controllers of viremia. Although plasma viral loads were undetectable, we could measure SIV-DNA by qPCR in peripheral blood mononuclear cells (PBMCs). Using these PBMCs, we screened 10 distinct PRR ligands to measure IFN-α and IFN-γ production. Among these, STING ligands, cGAMP and c-di-AMP, and the TLR7/8 agonist R848 markedly increased cytokine levels. Both R848 and STING ligands could reactivate latently-infected cells in both cynomolgus monkeys and human PBMCs in vitro . Furthermore, c-di-AMP increased the frequency of SIV Gag-specific CD8 + T cells including polyfunctional CD8 + T cells, as compared to that in untreated control or R848-treated cells. Together, STING ligands might be candidates for HIV treatment.